Seen & Heard. (Christian Century, 2026)
The article surveys faith-centered responses to modern crises, from AI-generated gospel artists to grassroots food recovery and real-world tests of religious compassion. Topics include ethical uses of artificial intelligence in ministry, urban gleaning as a response to food waste and hunger, and how religious institutions respond to immediate human need.